Implementasi Peraturan Presiden Nomor 67 Tahun 2021 Dalam Penanggulangan Tuberkulosis Paru di RSUD dr. Pirngadi - Simarmata, Riana Nopitasari; Hartono, Budi; Simamora, Beltahmamero (Strukturasi: Jurnal Ilmiah Magister Administrasi Publik, 2024)
This article or writing aims to determine the implementation and inhibiting factors of Presidential Regulation Number 67 of 2021 in controlling pulmonary TB at RSUD Dr. Pirngadi, Medan City. Data was collected through observation, interviews, documentation and triangulation to obtain accurate and in-depth information, and analyzed qualitatively.  This study concludes that the implementation of Presidential Decree Number 67 of 2021 at RSUD Dr. Pirngadi Medan City is running quite well. Presidential Decree Number 67 of 2021 has been socialized at RSUD Dr. Pirngadi to doctors, nurses and staff, but there has been no outreach to the community, but if patients seek treatment they have given instructions for pulmonary TB treatment. Dr. Hospital Pirngadi supports the pulmonary TB control policy with commitment and a sense of responsibility, good attitude of implementers in handling patients and those responsible for recording and reporting that runs well. The inhibiting factors are the lack of community role and the achievement of the recovery rate which is still below the national target because most patients who have not completed examination and treatment have already transferred treatment to referral health facilities.